2009
DOI: 10.2169/internalmedicine.48.2411
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Epithelioid Angiomyolipoma in the Kidney and Liver of a Patient with Pulmonary Lymphangioleiomyomatosis: Lack of Response to Sirolimus

Abstract: A 26-year-old woman with lymphoangioleiomyomatosis (LAM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
0
10
1
Order By: Relevance
“…Some reports suggested that mTOR inhibitors were effective in EAML [13]- [15]. On the contrary, others reported that mTOR inhibitors were not effective in EAML [16] [17]. The present case of EAML showed initially significant response to temsirolimus but rapidly progressed after cessation of temsirolimus therapy.…”
Section: Discussioncontrasting
confidence: 54%
“…Some reports suggested that mTOR inhibitors were effective in EAML [13]- [15]. On the contrary, others reported that mTOR inhibitors were not effective in EAML [16] [17]. The present case of EAML showed initially significant response to temsirolimus but rapidly progressed after cessation of temsirolimus therapy.…”
Section: Discussioncontrasting
confidence: 54%
“…Although there are few reports of angiomyolipomas in patients with LAM not associated with TSC, they are typically smaller, less frequently bilateral, and less prone to bleeding than those found in patients with TSC [11]. While one study reported an epithelioid angiomyolipoma in LAM [93], to our knowledge, an angiomyolipoma with epithelial cysts has not been reported in a patient with LAM not associated with TSC. The European Respiratory Society guidelines recommend that patients with unilateral angiomyolipomas, no clinical features of TSC, and no pulmonary symptoms, should be evaluated for LAM by undergoing HRCT of the chest [18].…”
Section: Angiomyolipoma In Lymphangioleiomyomatosismentioning
confidence: 93%
“…Higa et al reported a poor clinical response with rapid tumor growth after initiating a patient on sirolimus 15 . This result along with the poor clinical response from the patient presented in this report, lead one to postulate that inhibiting the mTOR pathway may at times only provide mild relief it at all in the progression of aggressive malignant EAML.…”
Section: Discussionmentioning
confidence: 55%